PENERAPAN MODEL STUDENT FACILITATOR AND EXPLAINING (SFAE) UNTUK MENINGKATKAN PRESTASI BELAJAR (Studi Pada Mata Pelajaran Ekonomi Siswa kelas X di SMA Negeri 1 Pagaralam) - Meliza Ikke Nurjana; Alexon Alexon (UNIB Press, 2021)
Objectives of this study are to: (1improve student achievement by applying thelearning model Student Facilitator and Explaining (SFAE). (2) Increase the effectiveness of student learning outcomes by applying the Student Facilitator and Explaining (SFAE)model learningin Economics learning at SMA Negeri 1 Pagar Alam. In this study, classroom action research (CAR) was used with three cycles and experiments. The research subjects were students of class X IPS SMA Negeri 1 Pagar Alam. The data collection techniques used in the study were the observation sheets and student test results. The data analysis usedmeanand t-test. The conclusions of this research are; (1The application of themodel Student Facilitator and Explaining can improve student achievement based on the results (research on high school students Negeri 1 Pagar Alam in Economics). (2) The application of themodel is Student Facilitator and Explaining effectively used to improve student achievement (research on students of SMA Negeri 1 Pagar Alam in Economics).